The influence of Islamic value and fraud diamond factors on academic fraud: Empirical study on Islamic University - Ajeng Kusuma Dewi; Abriyani Puspaningsih; Ataina Hudayati (al-Uqud : Journal of Islamic Economics, 2022)
The purpose of this study is to investigate the impact of Islamic values on Islamic behavior, Islamic environment, Islamic character education, and academic fraud diamond factors such as pressure, opportunity, rationalization, and capability. This research employs quantitative methods. The data was gathered using a questionnaire and a purposive sampling method, and it was analyzed using SPSS 19. The research sample consists of 259 Universitas Islam Indonesia students from all faculties. The findings of the study show that Islamic behavior, Islamic environment, and Islamic character education all have a negative impact on the perception of academic fraud. At the same time, pressure, opportunity, rationalization, and capability have no effect on academic fraud perception.